Sericulture as an Employment Generating Household Industry- A Case Study of Gayesbari Village of Kaliachak-I Block in Malda District, West Bengal - Aktar, Nasim; Sultana, Chand; Siddiqui, Shamsul Haque (National Geographical Journal of India, 2022)
Employment generation is one of the major potentials of Sericulture and Silk Industry in Malda district. Sericulture with its high employment potentiality and more income generation in the households itself has been identified as one of the major sources of rural development by empowering women through the financial self-dependent. Men and women have been contributing in all the stages starting from on-farm activities such as Mulberry plantation, indoor rearing of silk worm, feeding the silk worm, processing the cocoons etc. to off-farm activities. Present study has investigated the earning from sericulture as a livelihood in the Gayesbari village of Kaliachak-I Block of Malda District. A structured schedule was designed based on existing literature and used as an instrument for data collection. Collected data had been analyzed using standard statistical methods and final conclusion was drawn based on it. The study finds that sericulture is one of the most important sources of income, so most of the villagers are engaged in sericulture. I have selected the area due to the fact that KaliachakI block – the most intensive sericulture block in the district of Malda as well as in the state of West Bengal and as such it is the only block in the state where 04 (Four) Nos. of Technical Service Centre (TSC) of Sericulture are there with the support of biggest Cocoon Market of the state. Almost 70% of the district Sericulture has been confined in this block